KNOWLEDGE AND ATTITUDES OF MANAGERS ON THE APPLICATION OF STANDARDIZED MANAGEMENT SYSTEMS IN THE REPUBLIC HEALTH INSURANCE FUND - Tomanovic, Gorana (HEALTH CARE, 2023)
Introduction/Aim: The introduction and implementation of standardized management systems in the Republic Health Insurance Fund (RHIF) has become a necessity for the sake of internal stability, as well as the stability of the health system of the Republic of Serbia (RS). The aim of this cross-sectional study was to examine the knowledge and attitudes of managers of RHIF RS about standardized management systems and the importance of their implementation in RHIF, as well as to give appropriate recommendations.Methods: As part of this cross-sectional study, during May 2017, data was collected using a questionnaire from 157 managers of RHIF RS, because they had a direct insight into the implementation of ISO 9001 – quality management system and ISO 27001 – information security management system, for which RHIF is certified.Results: Of all the standardized management systems that were introduced in RHIF RS, the majority of managers were familiar with ISO 9001 (99.4%) and ISO 27001, while they were least familiar with ISO 30400 – human resources management system (6.4%), ISO 30001 – risk management system (5.7%), ISO 45001 – occupational health and safety (5.1%) and ISO 14001 – environmental management system (4.5%). The most important positive experiences regarding the implementation of ISO standardized management system were the following: better work organization (93.6%), increased satisfaction of employees (89.8%), improved work of branch offices (78.8%), and uniformity of work (72.0%), while the negative included: more extensive administration (26.8%) and resistance to changes (24.8%). The personal positive experiences related to the introduction of ISO standardized management systems included satisfaction with the improvement of business (84.1%) and increased responsibility (42.7%), while the negative ones were resistance to changes (31.2%) and a long period of introduction (23.6%).Conclusion: The continuous improvement of RHIF business process leads to the better quality of the healthcare system in RS and a better general health condition of society.
Keywords: knowledge, attitudes, managers, ISO standardized management system